Shoulder passive translation and rotation range of competitive elite female swimmers - McVann, A.; Jones, M.; Magarey, M.
The aim of this study was to determine if there was a significant difference in passive mobility between dominant and non-dominant shoulders of 15 asymptomatic elite female freestyle swimmers compared with dominant and non-dominant shoulders of a matched control group, who were not involved in swimming or any other regular overhead activity.